Response of the microbial community structure to the environmental factors during the extreme flood season in Poyang Lake, the largest freshwater lake in China - Zhang, Li; Yuan, Lijuan; Xiang, Jianjun; Liao, Qiegen; Zhang, Dawen; Liu, Jutao (Frontiers in Microbiology, 2024)
Background Poyang Lake is the largest freshwater lake in China, and there are several studies on the composition and diversity of bacteria in Poyang Lake, while few quantitative studies were carried out on the response of the bacterial community to environmental factors during the extreme flood season in Poyang Lake. Methods The connected-lake heterogeneity of bacterial community composition (BCC) was investigated in Poyang Lake during the flood season in 2020. Illumina high-throughput sequencing technology was used in this study. Results The bacterial community structure in the water was different from that in the sediment of Poyang Lake during extreme flood seasons. The bacterial diversity in water was much lower than that in sediment. In the water column, the dominant phyla were Actinobacteriota, while the composition of bacteria in sediment was more complex than that in water, and the dominant phyla in sediment were Proteobacteria, Chloroflexi, Acidobacteriota, and Actinobacteriota. The bacterial diversity in the water of Poyang Lake showed seasonal dynamics, while no seasonal variation of bacterial communities in sediment was observed. The bacterial community structure in the sediment from the two bays and channel areas of Poyang Lake can be distinguished from each other. The microbial diversity in sediment gradually increased from the Sancha Bay to the Zhouxi Bay and then to the channel, but the total nitrogen (TN) concentration in sediment (STN) and the total phosphorus (TP) concentration in sediment (STP) showed opposite trends. This might be due to the anthropogenic disturbances from the extreme flood. The bacterial community structure in, water column was significantly correlated with WT, NH4-N, STP, SOM, Chl a, DO, TP, and Eh, while the bacterial community structure in sediment was significantly correlated with SOM and STP. Conclusion The bacterial community structure in water was greatly different from that in sediment in Poyang Lake during extreme flood seasons. The bacterial community structure in the water column was not only sensitive to the geochemical characteristics of the water but also affected by some nutrient concentrations in the sediment. During the wet seasons, bacterial diversity was only affected by SOM and STP.